Cupronickel B10 and YG6 interface friction characteristics tested on a friction device for metal cutting. (November 2019) - Liu, Chunjian; Xu, Daochun; Li, Qingqing
Friction behavior is an important component of the metal-cutting mechanism. A simple and effective friction device that can yield the desired friction characteristics is required. In this article, a friction device with a solid–liquid–gas vibration reduction was proposed to research the interface friction characteristics. The interface friction characteristics of cupronickel B10 and YG6 were obtained through the new friction device, including the friction force, friction temperatures, and friction coefficient. The results show that an experimental solid–liquid–gas vibration reduction is feasible and effective to obtain the interface friction characteristics. The relationship between the friction-interface temperature T2 and the measured-point temperature T1 that was obtained by a heat-conduction model is linear. For cupronickel B10 and YG6, the friction coefficient gradually decreases with an increase in friction speed, and increases initially and then decreases with an increasing load. Based on the effect of friction temperature, friction speed, and load, a friction model for the interface friction characteristics of cupronickel B10 and YG6 was obtained.